The Efficiency Analysis of Food Crop Commodities - Setiawan, A B; ., Fafurida (KnE Social Sciences, 2018)
Grobogan is one of the main agricultural district, especially for food crops in Central Java. Paddy, corn and soybeans are potential agricultural commodities of Grobogan. The demand of these commodities is quite large. However, the productivity of paddy, corn, and soybeans in Grobogan turned out to be below the target set by the Government of Grobogan. It is required a means of identifying inefficiencies in paddy, corn, and soybeans which causes the production is under the target achievement. This study has a purpose is to look at how the level of efficiency of the use of factors of production in rice farming, corn, and soybeans in Grobogan. With the evaluation of the efficiency of some agricultural commodities in Grobogan, it is expected to be a basis of policy formulation in order to improve the agricultural sector in general and the welfare of farmers in particular. Food crop commodities where consist of paddy, corn, and soybeans are inefficient. In the calculation of technical efficiency, allocative efficieny and economics efficiency, all of that commodities have not efficient. These result have a recommendation to the farmers and stakeholders that the using of production factors should be decreased. Because, and inefficient of these commodities caused by over allocated of production factors. And also, inefficient condition assumed makes the government target of food croop commodities production could not been fulfilled Keywords: Food Crop, Paddy, Corn, Soybeans, Efficiency, Grobogan